One Pile Nim with Arbitrary Move Function - Holshouser, Arthur; Reiter, Harold (The Electronic Journal of Combinatorics, 2003)
This paper solves a class of combinatorial games consisting of one-pile counter pickup games for which the maximum number of counters that can be removed on each successive move equals f(t), where t is the previous move size and f is an arbitrary function.